Enhancing innovation in livestock value chains through networks: Lessons from fodder innovation case studies in developing countries - Ayele, Seife; Duncan, Alan J.; Larbi, Asamoah; Truong Tan Khanh (International Food Policy Research Institute, 2016)
Chapter 5 (Ayele et al.) analyzes the strategies and results of programs hosted by the International Livestock Research Institute (ILRI) to improve farmers’ welfare in Ethiopia, Syria, and Vietnam by integrating fodder production into their livestock systems. While fodder was an entry point for the innovation process, major improvements required that broader value-chain issues be addressed in a more holistic manner. The authors highlight the value of a national innovation policy and of government support for improving livestock farmers’ access to agricultural services, including credit and technological support.